Topic management and student initiation in an advanced Chinese-as-a-foreign-language classroom. Issue 1 (2nd January 2020) - Dolce, Frank M.; van Compernolle, Rémi A.
ABSTRACT: The focus of this article is on topic management and student initiation in the context of an advanced university-level Chinese-as-a-foreign-language class. Drawing on a corpus of 17.5 h of video-recorded classroom interactions, we focus on the ways in which students initiate topic expansions, thereby disrupting the IRF structure of discourse and enhancing learning opportunities. We identified three types of student-initiated topic expansions: genuine questions, topic elaborations and challenges to teacher assertions. We discuss our findings in relation to the enhancement of content and language learning opportunities, and we highlight several avenues for future research and implications for pedagogy.